2022
DOI: 10.1109/access.2022.3140588
|View full text |Cite
|
Sign up to set email alerts
|

Statistical H.264 Double Compression Detection Method Based on DCT Coefficients

Abstract: With the 2019 Coronavirus pandemic, we have seen an increasing use of remote technologies such has remote identity verification. The authentication of the user identity is often performed through a biometric matching of a selfie and a video of an official identity document. In such a scenario, it is essential to verify the integrity of both the selfie and the video. In this article, we propose a method to detect double video compression in order to verify the video integrity. We will focus on the H.264 compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Subsequently, transition probability matrices of the noise were used to detect doubly compressed video sequences. Mahfoudi et al demonstrated that DCT coefficients had a Laplacian distribution dependent on the quantization parameter used in the encoder [100], which could be used for double compression detection. Uddin et al investigated HEVC/H.265 [101] encoded videos and utilized both statistical and deep convolutional neural network features for multiple compression detection [102].…”
Section: Fingerprint-based Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, transition probability matrices of the noise were used to detect doubly compressed video sequences. Mahfoudi et al demonstrated that DCT coefficients had a Laplacian distribution dependent on the quantization parameter used in the encoder [100], which could be used for double compression detection. Uddin et al investigated HEVC/H.265 [101] encoded videos and utilized both statistical and deep convolutional neural network features for multiple compression detection [102].…”
Section: Fingerprint-based Detectionmentioning
confidence: 99%
“…The encoding parameters are also used extensively for double compression detection. In [100,102,199,204], the authors investigated double compression detection using encoding parameters in H.264 bitstreams. In [102,[205][206][207], the authors used encoding parameters in H.265 video bitstreams for double compression detection.…”
Section: Metadata Forensicsmentioning
confidence: 99%
“…The key will be given out if the matching score is lower than the threshold. Bottom-hat filtering, a straightforward and precise method for mining principal lines from palm prints, was introduced in [12]. Normalization, median filtering, average filters along four prefixed directions like 0, 45, 90, 135; grayscale bottom hat filtering; a combination of bottom hat filtering, binarization, and post processing; and so on are all examples of bottom hat filtering.…”
Section: Literature Surveymentioning
confidence: 99%
“…Recently, Li [ 27 ] proposed a semi-supervised learning method to detect double-compressed video using Gaussian density-based one-class classifiers. Mahfoudi proposed the statistical H.264 double-compression detection method based on discrete cosine transform (DCT) coefficients [ 28 ]. A motion-adaptive algorithm is proposed to detect HEVC double compression with the same coding parameters [ 29 ].…”
Section: Introductionmentioning
confidence: 99%